Semi-T-Hollow Modules and Semi-T-Lifting Modules - Elewi, Alaa A. (Iraqi Journal of Science, 2021)
Let be an associative ring with identity and let be a unitary left -module. Let be a non-zero submodule of .We say that is a semi- - hollow module if for every submodule of such that is a semi- - small submodule ( ). In addition, we say that is a semi- - lifting module if for every submodule of , there exists a direct summand of and such that The main purpose of this work was to develop the properties of these classes of module.